2014
DOI: 10.1139/cjfas-2013-0366
|View full text |Cite
|
Sign up to set email alerts
|

Individual condition, standard metabolic rate, and rearing temperature influence steelhead and rainbow trout (Oncorhynchus mykiss) life histories

Abstract: We reared juvenile Oncorhychus mykiss with low and high standard metabolic rates (SMR) under alternative thermal regimes to determine how these proximate factors influence life histories in a partially migratory salmonid fish. High SMR significantly decreased rates of freshwater maturation and increased rates of smoltification in females, but not males, after 1 year of rearing. Warmer water temperatures significantly decreased rates of freshwater maturation and increased rates of smoltification in both sexes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 60 publications
9
117
4
1
Order By: Relevance
“…Offspring from the above-waterfall resident population described earlier also produced significant numbers of smolts and returning anadromous adults despite over 70 years of complete selection against migration (see also Hayes et al 2012;. Likewise, freshwater maturation persists in many, if not all, hatchery steelhead trout stocks after decades of selectively breeding only anadromous adults (Christie et al 2011;Sharpe et al 2007;Sloat and Reeves 2014). Otolith microchemistry revealed that anadromous kelts in the Yakima River basin, Washington, had resident mothers 7% and 20% of the time in each of 2 years of study (Courter et al 2013).…”
Section: Oregon; Sloat and Reeves 2014mentioning
confidence: 86%
See 4 more Smart Citations
“…Offspring from the above-waterfall resident population described earlier also produced significant numbers of smolts and returning anadromous adults despite over 70 years of complete selection against migration (see also Hayes et al 2012;. Likewise, freshwater maturation persists in many, if not all, hatchery steelhead trout stocks after decades of selectively breeding only anadromous adults (Christie et al 2011;Sharpe et al 2007;Sloat and Reeves 2014). Otolith microchemistry revealed that anadromous kelts in the Yakima River basin, Washington, had resident mothers 7% and 20% of the time in each of 2 years of study (Courter et al 2013).…”
Section: Oregon; Sloat and Reeves 2014mentioning
confidence: 86%
“…"Steelhead" and "rainbow trout" are the common North American names for anadromous and freshwater resident life history forms of O. mykiss, respectively, whereas both forms are known as "mykizha" in Russia. Anadromous and resident forms are often sympatric, commonly interbreed, and their offspring may adopt either form (Christie et al 2011;Courter et al 2013;Sloat and Reeves 2014). The balance of life histories can vary, with some populations supporting more residents and others more anadromous individuals (e.g., .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations